The Hart sisters : early African Caribbean writers, evangelicals, and radicals - Ferguson, Moira; Gilbert, Anne Hart, 1773-1833; Thwaites, Elizabeth Hart, 1772-1833 (University of Nebraska Press, 1993)
Daughters of a black slaveholder father, Anne Hart Gilbert and Elizabeth Hart Thwaites were among the first educators of slaves and free African Caribbeans in late 18th and early 19th century Antigua. This is a collection of the writings of these members of the "free colored" community who married white men and played an active role in society.